Wind Tunnel Experiments and Field Observations of Aeolian Sand Encroachment around Vernacular Settlements in the Saharan and Arabian Deserts - Mohammed Fareed Sherzad; Dirk Goossens (Buildings, 2022)
One of the key repercussions of the desertification process in the Sahara and the Arabian desert is increased aeolian sand drift and sand deposition. Despite its isolated location and severe desert climate—particularly in terms of solar radiation, sand drift, and sand deposition—the region of El-Oued Souf in the Grand Erg Oriental in the Algerian Sahara has been a key cultural and trade center for many centuries. To resist the extreme weather conditions, the architecture of the vernacular settlements in the region of El-Oued Souf has unique design traits. Newly constructed buildings, on the other hand, frequently employ technologies based on models imported or imposed from climates that bear little resemblance to the desert. As a result, the inhabitants of these structures live more ‘in the desert’ than ‘with the desert’. This study investigates the impact and the effectiveness of vernacular desert architecture to resist aeolian sand encroachment problems in sandy desert areas. The sand accumulation patterns around vernacular buildings were identified and quantified using wind tunnel experiments. The size and shape of the buildings, as well as their geometric configuration within the settlement, were investigated in relation to the shape and dimension of sand accumulation formations. Field observations in north Algeria and the United Arab Emirates confirmed the accumulation patterns produced by the wind tunnel experiments. The study proposes possible design indicators for building forms to minimize the impact of sand deposition on such forms.